2015
DOI: 10.1007/s11356-014-3954-9
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic potential of PAHs in oil-contaminated soils from the main oil fields across China

Abstract: The concentrations, composition profiles, and sources of polycyclic aromatic hydrocarbons (PAHs) were analyzed in 55 surface soil samples collected from four oil fields across China (Daqing, DQ; Shengli, SL; Xinjiang, XJ; and Huabei, HB). The total 16 priority PAHs concentrations of DQ, SL, XJ, and HB ranged from 857 to 27,816; 480 to 20,625; 497 to 43,210; and 12,112 to 45,325 ng/g, respectively, with means of 9160; 6394; 13,569; and 22,954 ng/g and the seven possible carcinogenic PAHs accounted for 8-25.7 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Oil contamination of soils is a complex process and may lead to the destruction of natural habitats and harm the biota, including human beings, making the soil remediation a difficult but critical task (Zhu et al 2004;Ding et al 2010;Wang et al 2014). Nowadays, in situ biodegradation of contaminants is more preferred for its low-cost and less-invasive property compared to traditional ex situ techniques (Paerl et al 2003;Powell et al 2003;Berthe-Corti and Höpner 2005;Fine et al 1997;Sutton et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Oil contamination of soils is a complex process and may lead to the destruction of natural habitats and harm the biota, including human beings, making the soil remediation a difficult but critical task (Zhu et al 2004;Ding et al 2010;Wang et al 2014). Nowadays, in situ biodegradation of contaminants is more preferred for its low-cost and less-invasive property compared to traditional ex situ techniques (Paerl et al 2003;Powell et al 2003;Berthe-Corti and Höpner 2005;Fine et al 1997;Sutton et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al (2014) illustrated that NAs concentrations were 50e100 times higher than polycyclic aromatic hydrocarbons (PAHs) concentrations in the same sediment sample after oil spill. Our previous studies also showed that NAs concentrations in Daqing oil field was as high as 132.91 mg/kg, whereas the total PAHs concentration in the same soil sample was only 5.21 mg/kg (Wang et al, 2015a(Wang et al, , 2015b. These results indicate that NAs in oil spill-affected areas deserve more attention because of the potential toxicological risk they pose to the environment and human health.…”
Section: Introductionmentioning
confidence: 63%
“…High concentrations of NAs are frequently found in petroleum refinery wastewaters (Wang et al, 2013;Misiti et al, 2013), oil sands process-affected water (OSPW) (Rogers et al, 2002;Holowenko et al, 2002;West et al, 2013;Jones et al, 2012), and lixivium from oil sand storage sites in the Athabasca region of Alberta, Canada (Holowenko et al, 2002;Gagne et al, 2013). NAs are also found in coastal sediments (Wan et al, 2014), oil sands tailings (Herman et al, 1994;Holowenko et al, 2002;Armstrong et al, 2010), and oil polluted soils (Wang et al, 2015a(Wang et al, , 2015b. Wan et al (2014) illustrated that NAs concentrations were 50e100 times higher than polycyclic aromatic hydrocarbons (PAHs) concentrations in the same sediment sample after oil spill.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the concentrations of the ∑BapeqBPAHs were also calculated; the value was 430 μg kg −1 in AS, 1411 μg kg −1 in RS, and 936 μg kg −1 in VS. The ∑Bapeq16PAHs levels in the industrial district's soils are higher than those from soils found surrounding a thermal desorption plant in Zhejiang (67.0-479 μg kg −1 ) (Liu et al 2015), and from oilfield soils in Daqing (113 μg kg −1 ), Shengli (168 μg kg −1 ), Xinjiang (94.0 μg kg −1 ), Hebei (212 μg kg −1 ) (Wang et al 2015a). According to the Dutch government, uncontaminated soils that could be considered multi-usage soils should have a ∑Bapeq16PAH level of less than 20.0-50.0 μg kg −1 ( A n n o k k e e 1 9 9 0 ) .…”
Section: Risk Assessment By Bap Equivalent Concentrations (Bapeq)mentioning
confidence: 75%